2020
DOI: 10.1108/ecam-11-2019-0653
|View full text |Cite
|
Sign up to set email alerts
|

Effects of occupant behaviour on energy performance in buildings: a green and non-green building comparison

Abstract: PurposeOccupants are one of the most impacting factors in the overall energy performance of buildings, according to literature. Occupants’ behaviours and actions may impact the overall use of energy in more than 50%. In order to quantify the impact that occupant behaviour has in the use of energy, this study simulated interactions between occupants and the systems present in two actual buildings. The main aim was to compare the devia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…This approach could also result in cost savings, improved energy efficiency, reduced waste, and reduced GHG emissions [102,84]. By integrating energy simulation analysis with BIM, architects and engineers can examine the BEP at the early design stages and make necessary changes to achieve EE buildings [78,103]. BIM can also be used to identify the optimal orientation of the building, shading devices, and glazing types to optimize BEP [104].…”
Section: 5integrated Practice and Decision (Ipd)-making Using Bim (To...mentioning
confidence: 99%
“…This approach could also result in cost savings, improved energy efficiency, reduced waste, and reduced GHG emissions [102,84]. By integrating energy simulation analysis with BIM, architects and engineers can examine the BEP at the early design stages and make necessary changes to achieve EE buildings [78,103]. BIM can also be used to identify the optimal orientation of the building, shading devices, and glazing types to optimize BEP [104].…”
Section: 5integrated Practice and Decision (Ipd)-making Using Bim (To...mentioning
confidence: 99%
“…In their study, they found that the building occupants had less impact on the building energy use in the green-rated building, since this building was optimized from an energy use point of view. Therefore, green-rated buildings do not, by default, support building occupants to behave with energy awareness [12]. However, Darby et al [11] argued that the green-rated branding could work as a catalyst for energy awareness.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, researchers have noticed the importance of wellfunctioning building management. According to Almeida et al [12], a green-rated building must be operated by skilled personnel, otherwise the energy performance is at risk of performing at the same level as a non-rated building.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that buildings assessed with the LEED rating tool used more 28-35% energy. Almeida et al [18] investigated the impacts of occupant behavior on the energy performance of green and non-green buildings. The authors found that green buildings were inefficiently managed during the operational stage.…”
Section: Green Buildings Performancementioning
confidence: 99%